Characterization of cv. Cabernet Sauvignon (Vitis vinifera L.): the contribution of Ecklonia maxima seaweed extract - Samuels, Liam Jay (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScAgric)--Stellenbosch University, 2022.